Strategi Komunikasi Dalam Pembentukan Opini Publik Masyarakat - Siregar, Nurfitriani M. (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2021)
The discussion in this study is about communication strategies in the formation of public opinion, the research method used is library research, while the results of this study are several strategies that are used based on effectiveness in communication, namely cognitive, effective and conative. Meanwhile, in the formation of public opinion based on public relations, there are two activities used, namely internal and external.